Efektivitas Komunikasi Organisasi Dalam Memberikan Pemahaman Terhadap Peserta Aksi Demonstrasi di Sekolah Mahasiswa Progresif (Sempro) UNTIRTA - Muhammad Faisal Akbar; Nina Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Progressive Student School (SEMPRO) during a demonstration there were participants who did not understand what they were going to demonstrate. This could be caused by a lack of effective communication from the relevant organizations in providing a good understanding of the action participants. Therefore, research on the Effectiveness of Organizational Communication in Providing Understanding to Demonstration Participants at the Progressive Student School (SEMPRO) located on the Sultan Ageng Tirtayasa University (UNTIRTA) Campus needs to be carried out. This study uses a qualitative method. The results prove that communication greatly influences organizational success. Good communication between individuals and parties directly involved in the organization and parties outside the organization can develop good quality and performance to achieve common goals. To be able to develop effective communication, an active role is needed for all parties involved in the organization.